PELAKSANAAN FUNGSI KELUARGA DALAM RUMAH TANGGA PERNIKAHN DINI DI DESA KASANG LIMAU SUNDAI KECAMATAN KUANTAN HILIR SEBERANG - ", Lusiana; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research titled.” Implementation of family functions in early childhood marriage households in the Kasang Limau Sundaivillage Kuantan Hilir Seberang”.Then the researcher in interested this lifting thems because the fhenomena is insociety the early occur the teennageersin society in the kasang limau sundai village.Data analysis answer the problem that exsist in this study are analyzed in descriptive qualitative that analysis theories in the this research.(1)What reason cause early marriage in the Kasang limau Sundai.(2.How the implementation of family function in households that get marrrried at an early age.In data collection in this is observasion, interview, and documentation.As for the respondents in this is 12 people or 6 pairs of respondents.The research proves that early marriage the caused by economi factor, are one couples out of six couples because of the low economy they assume that marriage can support the family economy,and one pair of six couples is due to education or droping out of school,and four partner from six couples is due to being pregnant out of wedlock.while of family function early marriage do not properly becaused of assisted by parents.                                                                                                                                                                                                 Keywords   :Early Marriage, Teenagers, Family